Current status of high-risk HPV infection and correlation with multiple infections in cervical lesions in Western Guangzhou - Li, Jianqi; Lai, He; Qin, Honglei; Zhou, Dongmei; Zhao, Yang; Sheng, Xiujie (Frontiers in Medicine, 2024)
Objective This study aims to investigate the current status of multiple HPV infection and its association with cervical lesions in the western region of Guangzhou. Methods A retrospective analysis of clinical data from cervical cancer screening patients was conducted. The patients were grouped based on HPV genotypes and cervical pathology results to explore the prevalence of high-risk HPV infection and its relationship with cervical lesions in the western region of Guangzhou. The study also analyzed the relationship between high-risk HPV infection and cervical lesions among different age groups. Results A total of 13,060 patients were included in the study, with an overall infection rate of 18.46% (2,411/13,060). Among them, the infection rate of HPV genotype 16 was 14.14% (341/2,411), HPV genotype 18 was 5.23% (126/2,411), and other 12 high-risk HPV genotypes accounted for 71.96% (1,735/2,411). When comparing the incidence of HSIL+ (high-grade squamous intraepithelial lesion or worse) among different HPV genotypes, the results showed that the HPV 16 infection group (47.50%) had a higher incidence than the HPV 18 infection group (25.40%) and the other 12 high-risk HPV genotypes group (15.97%; P < 0.05). In the multiple infection groups, the pathogenicity rates were 63.64% (7/11) for the 16+18 HPV infection group, 42.97% (55/128) for the 16+other 12 high-risk HPV genotypes infection group, 26.79% (15/56) for the 18+other 12 high-risk HPV genotypes infection group, and 57.14% (8/14) for the 16+18+other 12 high-risk HPV genotypes infection group. These rates were significantly different compared to the single infection group (P <0.01). Although there was no statistically significant difference in the incidence of cervical cancer between the HPV 16 infection group and the HPV 18 infection group, both groups had a higher incidence compared to the group with other 12 high-risk HPV genotypes infection (P < 0.05). Further analysis suggests that the severity of cervical lesions is not associated with the number of high-risk HPV infections, i.e., the severity of cervical lesions is unrelated to multiple HPV infections but is instead related to the pathogenicity of the HPV genotypes. The infection rate and multiple HPV infection rate of women under 35 years old were higher than those of women aged 35 and above (20% vs. 17.1%; 2% vs. 1.3%; P < 0.05). Moreover, the pathogenicity rate of HSIL+ among high-risk HPV infection increased with age. Conclusions In the western region of Guangzhou, the overall infection rate of high-risk HPV is 18.46%. The severity of cervical lesions is unrelated to multiple HPV infections. The fundamental reason is the distinct pathogenicity of different HPV genotypes. The HSIL+ pathogenicity rates, from high to low, are in sequence for HPV 16, HPV 18, and the other 12 HPV types.